ADULT MIDGUT MALROTATION WITH LADD’S BAND: A RARE CASE REPORT WITH REVIEW OF LITERATURES - Hota, Prasan Kumar; Abhishek, D.; Bhaskar, V. (BALI MEDICAL JOURNAL, 2014)
Background: Midgut malrotation is an anomaly of intestinal rotation that occurs during fetal  development and usually presents in the neonatal period. It is rare for midgut malrotation to present in  adulthood. Method: We present a case of 15 year old girl presenting with acute abdomen of 15 days  duration. Clinical evaluation and investigations revealed features of acute small gut obstruction with  peritonitis. Patient underwent exploratory laparotomy which revealed Ladd ? s band with midgut  malrotation with gangrenous and perforated duodeno-jejunal segment. Derotation with release of band  with appendicectomy and resection of gangrenous segment with end to end anastomosis and  anatomical repositioning of the bowel was performed. Results: Complete resolution of symptoms seen  in 4 months follow-up. We report this case for the rarity of the case with an unusual presentation of  adult midgut malrotation due to Ladd?s band presenting with gangrene of the affected gut with  perforation, which was managed successfully.
Keywords: Mid gut malrotation; Ladd?s band; Ladd?s procedure.